Intellectual and developmental disabilities research centers: Fifty years of scientific accomplishments. Issue 3 (27th July 2019) - Walkley, Steven U.; Abbeduto, Leonard; Batshaw, Mark L.; Bhattacharyya, Anita; Bookheimer, Susan Y.; Christian, Bradley T.; Constantino, John N.; de Vellis, Jean; Doherty, Daniel A.; Nelson, David L.; Piven, Joseph; Poduri, Annapurna; et al.
Abstract : Progress in addressing the origins of intellectual and developmental disabilities accelerated with the establishment 50 years ago of the Eunice Kennedy Shriver National Institute of Child Health and Human Development of the National Institutes of Health and associated Intellectual and Developmental Disabilities Research Centers. Investigators at these Centers have made seminal contributions to understanding human brain and behavioral development and defining mechanisms and treatments of disorders of the developing brain. ANN NEUROL 2019;86:332–343